Clinical Course and Disease`s Outcome Aspects of COVID-19 Pediatric Patients in Ibn Al-Khateeb Isolation Hospital - Oleiw, Abbas Oweid; Habib, Kholod Dhaher; Mohammed, Kadhim Abed; Abbas, Oday Yassen; Jaber, Zainab Ali (AL-Kindy College Medical Journal, 2021)
Background: Corona virus disease 2019 (COVID-19) is a communicable disease caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). It was first identified in December 2019 in Wuhan, China, and has since spread globally, leading to an ongoing pandemic. Aim of study: to review the clinical, lab investigation and imaging techniques, in pediatric age group affected COVID-19 to help medical experts better understand and supply timely diagnosis and treatment. Subjects and methods: this study is a retrospective descriptive clinical study. The medical records of patients were analyzed. Information’s recorded include demographic data, exposure history, symptoms, signs, laboratory findings, chest x- ray, and chest computed tomographic (CT) scans. Data were obtained with data collection forms from paper medical records. Results: there were 76 COVID-19 pediatric patients, 46.1% of those patients were within the age group 6 -10 years. The female to male ratio was 1:1, and 92.1% of them were living within the urbane area. About 60.5% of patients were pupils. Seventy-one (93.4%) patients of them had no comorbidity. Twenty (26.3%) patients were asymptomatic. Regarding the duration of hospital stay, 39(51.31) patients had <7 days. All of the patients were nonsmokers. All patients had recovered and discharged from hospital after 2 negative real technique-polymerase chain reaction (RT-PCR) tests, no death was reported. Only 16(21.1%) patients had severe symptoms. Conclusions: the most common symptoms were fever, Cough, Loss of appetite, Shortness of breath & Fatigue. There was a statistically significant association between white blood cells counts, neutrophil number, Chest X-Ray results, with case severity and a statistically significant association between form of treatment in patients who received Oxygen, Oseltamivir, Azithromycin, Paracetamol, Dexamethasone, and case severity.